2020
DOI: 10.1016/j.scitotenv.2020.141036
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide and veterinary drug residues in Belgian beeswax: Occurrence, toxicity, and risk to honey bees

Abstract: Pesticide and veterinary drug residues are one of the stress factors affecting bee health and mortality. To investigate the occurrence, the concentration and the toxicity risk to bees of pesticide residues in four different types of beeswax (brood comb wax, recycled comb wax, honey comb wax, and cappings wax), 182 samples were collected from apiaries located all over the Belgian territories, during spring 2016 and analysed by LC-MS/MS and GC-MS/MS for the presence of 294 chemical residues. The toxicity risk to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 66 publications
2
41
0
Order By: Relevance
“…The benefits of comb management support previous research that showed that newer comb better support honey bee colony health and reproduction (Berry and Delaplane, 2001). Beeswax has been shown to accumulate pesticide residues (Calatayud-Vernich et al, 2018;El Agrebi et al, 2020a), to levels that could result in increased bee mortality (El Agrebi et al, 2020b). Though colony-level effects (growth and survivorship) from wax contamination had not been confirmed through field trials (Payne et al, 2019), where the authors noted that Varroa levels were a far stronger predictor of colony failure.…”
Section: Improved Management Practicessupporting
confidence: 63%
“…The benefits of comb management support previous research that showed that newer comb better support honey bee colony health and reproduction (Berry and Delaplane, 2001). Beeswax has been shown to accumulate pesticide residues (Calatayud-Vernich et al, 2018;El Agrebi et al, 2020a), to levels that could result in increased bee mortality (El Agrebi et al, 2020b). Though colony-level effects (growth and survivorship) from wax contamination had not been confirmed through field trials (Payne et al, 2019), where the authors noted that Varroa levels were a far stronger predictor of colony failure.…”
Section: Improved Management Practicessupporting
confidence: 63%
“…links to adverse effects at individual bee‐level or at the colony‐level. The use of the HQ threshold in assessing the risk posed by residues in wax 7,11,13,14,19,20 (or for solitary bees in soil 37 ), where contact transfer factors for compounds are required, 38,39 and in dead bees, 11,14,18,21 without relating to residues following exposure at the LD 50 are not defined, 40 are even more obscure. To compound matters, in assessing the significance of residues in pollen and nectar, the contact LD 50 has also been used, 2,9,13,17 or even an ‘average’ of acute toxicity values, 11,12,18 even though the acute oral LD 50 is clearly more relevant for this exposure route.…”
Section: Erroneous Conclusion Resulting From the Use Of The Hazard Quotient To Evaluate Residue Data From Pollen And Nectarmentioning
confidence: 99%
“…According to Mitchell et al [58], residues of neonicotinoids were detected in a variety of honey samples all over the world. Moreover, application of plant protection products in both urban and rural areas can lead to bee products' contamination [59,60]. Several contaminations by glyphosate were reported in Germany and one organic beekeeper had to destroy a significant amount of honey due to the exceeding the maximum residue levels of glyphosate [61].…”
Section: Discussionmentioning
confidence: 99%
“…Bee products' contamination may threaten the future of many beekeepers; however, organic beekeeping can bring certain benefits in case of these residues. Furthermore, organic beekeeping can solve the problems with residues from chemical treatments against Varroa, mainly from application of acaricides, which can create residues in bee products [59,63].…”
Section: Discussionmentioning
confidence: 99%